Ultrasonic characteristics of inserted central catheter related fibroblastic sleeve - Zhifei Ben; Jue Wang; Jinyong Zhan; Kaiying Xu (Scientific Reports)
Abstract This study was aimed to summarize the ultrasonic characteristics of inserted central catheter (ICC) related fibroblastic sleeve, providing theoretical basis for its early diagnosis. Clinical and ultrasonic data of patients with ICC confirmed by pathology to have fibroblastic sleeves in our hospital from June 4, 2020 to April 1, 2024 were collected. All ICCs were made of polyurethane. Patients required the ultrasound evaluation due to local swelling and pain, abnormal coagulation function, lack of response to flushing of saline and heparin, or before extubation. The ultrasonic characteristics of fibroblastic sleeve such as its starting point, shape, thickness, internal echo, number of layers, relationship to the catheter, and presence or absence of thrombosis were analyzed. After the removal of the ICC, there was a membrane-like structure adhesion on the surface of the catheter, which was composed of endothelial cells, smooth muscle cells, collagen and fibrous connective tissues. A total of 95 patients with pathologically confirmed fibroblastic sleeve were present, of which 44 patients had only fibroblastic sleeves (46.32%) and 51 patients had fibroblastic sleeves with thrombi (53.68%). The fibroblastic sleeve originated from the site where the catheter contacted the vein wall and extended in a distal direction, with a thickness ranged between 0.7  and 5.6 mm. With the pathological results as the gold standard, the optimal cut-off value for the diagnosis of fibroblastic sleeve with thrombosis was 2.58 mm, and the sensitivity and specificity of the diagnosis were 95.45% and 96.08%. Compared to echogenicity of the catheter wall, hyperechoic or isoechoic fibroblastic sleeves were observed in 89 patients, while hypoechoic fibroblastic sleeves were observed in 6 patients. There were significant differences in the location of catheterization and duration of catheterization between the single-layer group and the double-layer group (P < 0.05). Fibroblastic sleeves were tightly attached to the catheter walls in 78 patients and loosely attached to the catheter walls in 17 patients, with significant differences in the location of catheterization and duration of catheterization (P < 0.05). ICC-related fibroblastic sleeves have specific ultrasonic characteristics. Understanding these ultrasonic characteristics can provide a reliable basis for their early diagnosis and timely treatment.